Сhina: Toward a Market-based Open Innovation System - Xielin Liu; Nannan Lundin (Foresight and STI Governance)
The rapid growth of Chinese economy in the last two decades is an essential result of an effective state policy for its transformation into an open and market form. Similar changes took place in innovation system. The emphasis is placed on the cooperation of science and business, the commercialization of scientific research outcomes. As a result - the activities of certain high-tech companies in China have already acquired global scales, while China itself has become an extremely attractive location for manufacturing and research centers by foreign multinationals.